Identification of Factors Affecting a Business Model Using a Fuzzy Approach - Fattah Peiravian; Azim Hosseini (مهندسی و مدیریت ساخت)
The present study was an attempt to identify the factors influencing business model using the multi-criteria decision-making approach. Review of the literature on business models shows that competitive models and Porter's value chain play a vital role in business models. In the present study, the experts of Mohandesi Sazan construction and sale Company investigate the critical foundations of business model, the importance of Porter's value chain and different elements of competition in order to evaluate and prioritize Porter's competitive models and value chain. The instruments used in this study include a pairwise comparison questionnaire and the AHP hierarchy technique in the EXCEL software. The population of the study consisted of experts and managers of Mohandesi Sazan Company in Shiraz (10 individuals). Five members of the population were selected using snowball sampling method. According to the results obtained from analysis of data collected from 5 experts, the bargaining power of suppliers is the top ranking element in the competitive model. The results also showed that the primary activities transcend the support activities in the value chain model. The evaluation of the sub-criteria associated with the primary activities showed that marketing is the top-most priority among other sub-criteria while evaluation of the sub-criteria associated with support activities suggested that firm architecture outweighs other sub-criteria.